20,000 leagues under the sea - Verne, Jules, 1828-1905.; Harper Collins (London : Harper Collins, 2010)
An American frigate tracks down a ship-sinking submarine commanded by the mysterious Captain Nemo.
Young Adult
Keywords: Submarines (Ships) -- Fiction; Underwater exploration -- Fiction; Sea stories; Submarines -- Fiction